2014
DOI: 10.1038/oncsis.2014.38
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPβ expression is an independent predictor of overall survival in breast cancer patients by MHCII/CD4-dependent mechanism of metastasis formation

Abstract: CCAAT-enhancer binding protein β (C/EBPβ) is a transcription factor that has a critical role in mammary gland development and breast cancer progression. Loss of C/EBPβ increases metastatic dissemination of mouse mammary tumor cells. However, the mechanism by which C/EBPβ expression affects metastasis formation remains unknown. This study aims at determining the relationship between C/EBPβ and survival of breast cancer patients, and elucidating C/EBPβ's link with metastasis formation. C/EBPβ expression was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…In support of this, reduced staining of CEBPB was observed in samples of ductal breast carcinomas shown in the Human Protein Atlas database [55]. Furthermore, thte expression of CEBPB was reported to be an indicator of metastasis and overall survival in breast cancer patients [56].…”
Section: Discussionmentioning
confidence: 71%
“…In support of this, reduced staining of CEBPB was observed in samples of ductal breast carcinomas shown in the Human Protein Atlas database [55]. Furthermore, thte expression of CEBPB was reported to be an indicator of metastasis and overall survival in breast cancer patients [56].…”
Section: Discussionmentioning
confidence: 71%
“…CEBPB is closely related with lipid metabolism in HepG2 cells and liver cancer cells . CEBPB expression is associated with overall survival in breast cancer and gastric cancer patients . In Ewing sarcoma and ovarian cancer, CEBPB could promote tumor cell resistance to chemotherapy .…”
Section: Discussionmentioning
confidence: 99%
“…57,58 CEBPB expression is associated with overall survival in breast cancer and gastric cancer patients. 59,60 In Ewing sarcoma and ovarian cancer, CEBPB could promote tumor cell resistance to chemotherapy. 61,62 In this study, we found that CEBPB promotes the transcription of CPT1A and activates FAO.…”
Section: Discussionmentioning
confidence: 99%
“…While the overexpression of LAP isoforms determines cell cycle arrest or differentiation, as shown in hepatocytes, hematopoietic cells and adipocytes, LIP induces proliferation and contributes to tumor cells survival. Increased LIP expression antagonizes LAP activity and the high LIP:LAP ratio favors c-myc activation and inactivation of cell cycle inhibitor genes [131,135]. LIP isoform contributes to cell survival and tumor progression, as demonstrated in hepatoma cells.…”
Section: Ccaat-enhancer Binding Protein β (C/ebpβ)mentioning
confidence: 97%